Cerita seru panca dan sila: Inovasi buku berjenjang untuk literasi membaca - Siti Rochmiyati; Tri Nafiah (Indonesian Journal of Learning and Educational Studies, 2026)
Literacy reading skills, especially elementary school students, are crucial aspects. However, there is still a lack of quality books, particularly at the C level (Semenjana). The purpose of this research is to create a tiered storybook with Pancasila Student Profile content in digital and print formats. The research method used is a research and development (R&D). The research subjects consist of 21 school principals, 5 teachers, and 10 fifth-grade students from several elementary schools in  Moyudan District, Sleman, Yogyakarta. Data were collected through questionnaires, interviews, observations, and documentation. Data analysis was conducted descriptively qualitatively and quantitatively. The result of this research is an analysis of the needs that are suitable for students' needs to create a tiered storybook product named "Cerita Seru Panca and Sila" containing all dimensions of the Pancasila Student Profile accompanied by a reading learning module for fifth-grade that has been validated as suitable by experts and stakeholders. With this product, it is hoped that students can enjoy a pleasant reading experience while enhancing their literacy.